LARAST Apps Administration Public Service Using Restful Api Method and MVVM Architecture - Fifit Alfiah; Herfandi Herfandi; Aditya Agus Wisanto (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
Technological developments have made it easier for users both in terms of speed and accuracy in the transition to accessing an application. This convenience in particular gives rise to an idea and idea to be able to create an administrative service application that is used by the community around the Pasar Kemis sub-district. In the administrative service process, they still use queue numbers and for the filing process, they still use duplicated files by photocopying. The duplication resulted in an archive field at the Pasar Kemis District office. The submission of the completed application file does not have the correct information for file retrieval, so valid information is needed regarding the completion of the application file. This application uses the Restful API in the Laravel framework and implements its security using the Laravel Passport as a JSON access token key. Larast Apps uses the MVVM architecture. For HTTP Client Server using Retrofit 2 and OkHttp and Kotlin Coroutines. With this application, it can simplify the process of submitting public administration services. Submitting an application from home through the Android application can avoid crowds at the Pasar Kemis District Office and cut down on the bureaucracy that is already running properly.